A novel wireless charging system for GIS state observation video sensor. (April 2022) - Wen, Feng; Zhao, Wenhan; Chu, Zhoujian; Zhang, Guoqi; Zhang, Xiang; Zhang, Dashang; Ma, Jianxing; Yao, Zhijun
Abstract: Because the gas insulated switchgear (GIS) is closed, it is impossible to directly see the actual position of internal contacts. The image recognition technology can be used to collect, analyze and process the images of the switches in different states, and finally obtain the actual opening and closing state. In addition, some potential flaws can also be identified in advance. Considering the particularity of the GIS internal environment, wireless charging system can be used to supply power for internal video sensor. In this paper, a new type of coupling coil structure, DC coil, is proposed, which supplies power for video sensor through GIS observation window by wireless power transfer (WPT) technology. The proposed DC coil is analyzed theoretically, optimized by genetic algorithm (GA), and verified by finite element method (FEM). The experimental results indicate that the proposed structure can achieve the same transfer performance in lateral and rotation misalignment, while the conductor and space is saved by 8.49% and 22.22% compared with the traditional DD coil. The proposed DC coil is feasible to be applied in the actual GIS scene.